2023
DOI: 10.1186/s12872-023-03038-9
|View full text |Cite
|
Sign up to set email alerts
|

Upgulation of lncRNA GASL1 inhibits atherosclerosis by regulating miR-106a/LKB1 axis

Abstract: Background Atherosclerosis (AS) is a common frequently-occurring disease in the clinic and a serious threat to human health. This research aimed to explore the value between GASL1 and AS. Methods The expression and values of GASL1 in AS patients were revealed by qRT-PCR and ROC curve. The HUVEC cells were induced by ox-LDL to construct in-vitro models. Cell viability was detected by MTT assay, and apoptosis was detected by flow cytometry. The infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…Mounting evidence suggests that lncRNA dysregulation is closely associated with human diseases, including atherosclerosis, where they play significant roles. For instance, the lncRNAs H19, TUG1, and Neat1 are upregulated in atherosclerosis and contribute to vascular smooth muscle cell (VSMC) proliferation while inhibiting apoptosis On the other hand, the downregulation of UCA1, MEG3, lincRNA-p21, and GASL1 in atherosclerosis leads to suppressed VSMC proliferation and inflammation [8,[38][39][40]. In our previous research, we observed increased expression of miR-19a-3p in the serum and atherosclerotic plaques of patients with atherosclerosis.…”
Section: Discussionmentioning
confidence: 93%
“…Mounting evidence suggests that lncRNA dysregulation is closely associated with human diseases, including atherosclerosis, where they play significant roles. For instance, the lncRNAs H19, TUG1, and Neat1 are upregulated in atherosclerosis and contribute to vascular smooth muscle cell (VSMC) proliferation while inhibiting apoptosis On the other hand, the downregulation of UCA1, MEG3, lincRNA-p21, and GASL1 in atherosclerosis leads to suppressed VSMC proliferation and inflammation [8,[38][39][40]. In our previous research, we observed increased expression of miR-19a-3p in the serum and atherosclerotic plaques of patients with atherosclerosis.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, the concentration of 11 circulating miRNAs was altered during the intervention, including miR-106a, which correlated with the change in plasma EPA levels and TG levels [ 50 ]. miR-106a has recently been suggested to play a role in the development of atherosclerosis [ 65 ]. Moreover, miR-122 and miR-33 are important regulators of lipid metabolism, controlling the expression of genes in fatty acid and cholesterol metabolism, including fatty acid synthase ( FAS ), sterol regulatory element binding transcription factor 1 ( SREBF1 ), ATP binding cassette subfamily A member 1 ( ABCA1 ), ATP binding cassette subfamily G member 1 ( ABCG1 ) and carnitine palmitoyltransferase 1A ( CPT1A ) [ 66 , 67 ].…”
Section: Non-coding Rna and Tg Response To Omega-3 Fatty Acid Supplem...mentioning
confidence: 99%